Location and size are useful features in diagnosing sessile serrated adenoma/polyp - Hasnan Najib, Shahril Fikri Zul; Mohamed Shabery, Noor Afidah; Hussin, Huzlinda (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: According to the predefined 2010 World Health Organisation criteria, serrated colonic polyps (SCP) are pathologically classified into hyperplastic polyp (HP), sessile serrated adenoma/polyp (SSA/P) with or without cytological dysplasia and traditional serrated adenoma (TSA). Sessile serrated adenoma/polyp is acknowledged as a precursor of colorectal carcinoma through the serrated neoplastic pathway. Hyperplastic polyps display similar histological features to SSA/P, in comparison to other types of SCP. It is noteworthy to discriminate between HP and SSA/P, since only the latter has a malignant potential. Method: A total of 198 cases of SCP were identified and the slides were reexamined and reclassified accordingly. Analysis on the proportion of SSA/P among SCP and underdiagnosed cases of SSA/P was performed. The association between SSA/P and non-SSA/P with demographic data and colonoscopic findings were also studied. Results: From the 198 cases of SCP, 164, 29 and five cases were reclassified as HP, SSA/P and TSA respectively. Sixteen cases of SSA/P were underdiagnosed as HP. From among 29 cases of SSA/P, the majority were ≥ 65 years old (17; 58.6%), male (21; 72.4 %) and Chinese (17; 58.6%). Most of the SSA/P (16; 55.2 %) were located in the right colon and measured ≥ 10mm (9; 31%) in size. Location (p=0.004) and size (p=0.013) of the colonoscopic findings were significantly associated with SSA/P. Conclusion: Underdiagnosed cases of SSA/P among HP were identified most likely because of the resemblance of their histological features. The location and size of SCP may suggest the probability of SSA/P.